M23 Does pseudomonas aeruginosa colonisation cause more rapid decline in FEV1 in non-cystic fibrosis bronchiectasis?. (12th November 2019) - Millington, K; Hamilton, F; Casey, H; Easton, F; Malin, A
Abstract : Background: Cystic Fibrosis (CF) colonisation with Pseudomonas aeruginosa (PSA) is associated with decline in pulmonary function. In non-CF bronchiectasis this link is unclear. We carried out a retrospective review of a large cohort of non-CF bronchiectasis patients to determine if pulmonary function decline is associated with PSA colonisation. Method: A retrospective review of a non-CF bronchiectasis cohort in a large District General Hospital was performed. Database-driven, electronic patient records from the bronchiectasis service were reviewed. Baseline patient data including PSA infection were collected and categorised into three groups: never infected (p=72); intermittently isolated (p=41); and colonised (p=118). PSA culture on more than one occasion within 3 months defined colonisation. Forced expiratory volume in one second (FEV1) measurements were collected longitudinally from the first ever encounter through to July 2018. Linear regression was performed to look at Year 1 and Year 3 FEV1 measurements. Covariates included first ever FEV1 recorded (as the baseline measure of lung function), Non-tuberculous mycobacterium (NTM) disease, BMI, previous admission status, age, and PSA colonisation. In addition, a second analysis was performed for PSA colonisation and FEV1 alone to specifically look at this effect, given gaps in the data for some of the other covariates. All analyses were performed using the glm function in R 3.6.0. Results: 231 patient records were reviewed. A number of models were generated to analyse the data (table 1). Initial FEV1 was strongly associated with subsequent FEV 1. PSA colonisation was linked with Year 1 FEV1 in univariate analysis, but once covariates were added, this relationship disappeared. No other variable was significantly associated with FEV1 at either outcome time (Year 1 or Year 3). Conclusion: To our knowledge this study assesses the largest cohort of PSA colonised patients against lung function decline. Patients colonised with PSA appeared to have poorer initial lung function than patients never infected or patients intermittently isolated with PSA. We have found no evidence of an association with ongoing decline in lung function with PSA colonisation. This suggests PSA as a marker of disease severity rather than a cause.